Urgensi Pendidikan Kewarganegaraan Global dalam Kurikulum Pendidikan Pancasila dan Kewarganegaraan di Abad 21 - Usmi, Rianda; Samsuri, Samsuri (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to describe the urgency of global civic education, civic education in the Indonesian context, and the conceptual framework of global civic competencies in developing the Pancasila and civic education curriculum. This study used a descriptive qualitative approach with a literature study method through several stages, including collecting library data, taking notes, reviewing data sources, and processing information. The urgency of global citizenship education was to prepare young people who understand the contemporary world, play an active role in solving national and global problems, and become proactive contributors to a more just, peaceful, tolerant, inclusive, safe, and sustainable world. Pancasila and civic education in the Indonesian context did not yet contain material for global civic education. The conceptual framework for global civic in developing the Pancasila and civic education curriculum should include three main elements: global knowledge and understanding, values and attitudes, and global skills.